(untitled) (Journal of Philosophy, Culture and Political Science, 2024)
National feeling – love for the nation, compassion, the ability to appreciate the heritage of the people, recognizing their national representation. Everyone should know and respect other nations through pride in their homeland, deep love for their nation. The main means of forming natio:nal consciousness is the native language,one of the foundations of forming consciousness, which has great support in establishing the continuity of Virtue and patriotic values. Today, the education of the younger generation as a creative person with a deep understanding of the history, surname, traditions, language of their people, human culture, human qualities is a requirement of life, a necessity of society. The law of the Republic of Kazakhstan on Education defines the main positions of the state policy of comprehensive education and upbringing of the younger generation. These are: the equal right of all humanity of the Republic of Kazakhstan to education, the intellectual development of each humanity, psycho-physiological and personal characteristics, the opening of a wide path to all levels of education for the population. That is, in the law of Education, based on the right of every citizen to education, there is a need to comprehensively cover the process of training, education, development, formation of didactic conditions in the formation and education of respect for the national values of young people. For the formation of national values in young people, we should focus on the issues of national culture, traditions, folk teachings, etc. Kazakh culture is a national culture formed over the centuries. It was developed and formed on the basis of National Education. National Education is the driving force behind the development of the culture of that nation. Each people has a historical existence and spiritual experience. The educational and worldview views of the people, formed through their spiritual practices in life, we call folk pedagogy. Folk pedagogy is the cultural heritage of the people. Folk pedagogy developed and formed in connection with the (national) ethnic characteristics of that people. Key words: education, traditional, consciousness, morality, social, intelligence, self-improvement, generation